Environmental and mechanical performance of different fiber reinforced polymers in beams - Sami Sbahieh (17563119) (2022)
The worldwide awareness toward sustainability motivated the human innovativeness to investigate and apply additional environmental solutions like the use of fiber-reinforced polymer (FRP) as a reinforcement instead of steel in order to lower the greenhouse emissions and energy consumption associated with the excessive structural work. The deterioration of structural members is always expected due to many factors such as corrosion of steel, severe weather and unexpected loads, therefore the use of fiber-reinforced polymers gained popularity due to their advantageous properties such as lightweight, high strength and corrosion resistance. The arising concerns about climate change and depletion of natural resources paved the way to conduct comprehensive studies to assess the environmental impact of FRP during its life service. Life cycle assessment is used to evaluate the environmental impact of a product or a process. This paper seeks to contribute to the existing literature of studies related to the life cycle assessment, mechanical behavior, and the applications of different FRP composites used as a reinforcement in concrete beams. The reported results from literature were compatible with each other where using FRP composites in beams enhance the stiffness and strength and at the same time reduce the environmental impacts compared to traditional building materials like steel, also developing the design and construction codes for reinforced concrete beams by using FRPs will encourage the use of these materials in constructions. Other Information Published in: Materials Today: Proceedings License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.matpr.2022.04.398